Application of the biochar-based technologies as the way of realization of the sustainable development strategy - Daria Gasior; Wilhelm Jan Tic (Economic and Environmental Studies (E&ES), 2017)
The technologies of thermal processing of biomass, biowaste or sewage sludge into biochar as well as its potential use in the industry, power industry, housebuilding industry, agriculture or environmental protection attract growing attention. The multi-faceted, unique properties of biochar make it particularly attractive from the point of view of the achievement of sustainable development goals according to which the needs of the present generation should be satisfied in such a way so as not to harm the environment and in such a way that the future generations could use the same natural environment as we do. The EU policy focusing on the implementation of the principles of sustainable development emphasises the need to reduce the exploitation of natural resources, to use effective technologies processing waste and to develop new biodegradable and environmentally friendly products. Due to the wide range of biochar applications in many economy sectors, the ways of production, ensuring the reduction of waste generation, and its economic attractiveness, this product meets the expectations of the sustainable development policy. The aim of this paper is review the biochar-based technologies and the concepts of its application, and description of the disadvantages and advantages each of them..
Keywords: Q53; Q20; 330; sustainable development; biochar; reducing of CO2 emission; thermal processing of biomass